2023
DOI: 10.1088/1748-9326/acbe51
|View full text |Cite
|
Sign up to set email alerts
|

Identifying determinants of pesticide use behaviors for effective agri-environmental policies: a systematic review

Abstract: Environmental problems demand for innovative interdisciplinary research to tackle problem complexity and provide insights for problem-solving. Along these lines, behavioral insights have the potential to improve the effectiveness of policies by identifying which behaviors are best tackled and how. In this paper, we present a systematic review of the literature on small-scale farmers’ pesticide use in the Global South to identify (1) pesticide use behaviors and (2) their behavioral determinants. We defined our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 111 publications
(66 reference statements)
2
3
0
Order By: Relevance
“…This finding is consistent with the existing studies regarding the positive association between intention and adoption in the context of sustainable agriculture (Foguesatto et al. , 2020; Wiedemann and Inauen, 2023) and confirms the importance of “capturing” and “cultivating” good intentions for sustainability on behavior change in practice. The more ready farmers are for the sustainability transition, the more likely they are to adopt sustainability tools (Kallas, 2019; Kim et al.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the existing studies regarding the positive association between intention and adoption in the context of sustainable agriculture (Foguesatto et al. , 2020; Wiedemann and Inauen, 2023) and confirms the importance of “capturing” and “cultivating” good intentions for sustainability on behavior change in practice. The more ready farmers are for the sustainability transition, the more likely they are to adopt sustainability tools (Kallas, 2019; Kim et al.…”
Section: Resultssupporting
confidence: 92%
“…The path coefficient of the sustainability transition intention to use sustainability tools is significant, indicating that farmers who intend to transform their farms are more likely to adopt sustainability tools. This finding is consistent with the existing studies regarding the positive association between intention and adoption in the context of sustainable agriculture (Foguesatto et al, 2020;Wiedemann and Inauen, 2023) and confirms the importance of "capturing" and "cultivating" good intentions for sustainability on behavior change in practice. The more ready farmers are for the sustainability transition, the more likely they are to adopt sustainability tools (Kallas, 2019;Kim et al, 2019).…”
Section: Structure Equation Modelingsupporting
confidence: 91%
“…Contrary to our study, the systematic study by Afshari and et al (2021), which was conducted on interventional studies in the field of reducing exposure to pesticides in farmers, showed that most studies were conducted in developed countries, including the United States [ 57 ]. Wiedemann and colleagues in a systematic study showed that in developing countries, extension services cannot reach the entire agricultural community due to insufficient budget [ 58 ]. In wealthy and developed countries, strict regulations have been imposed for the use of pesticides, and exposure to toxic chemicals is prohibited or limited for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to understand the optimal levels of pesticide use and their implications for both productivity and environmental conservation to shape sustainable agricultural policies [9], [13]. This requires a holistic approach that considers factors such as farmer behavior, agricultural practices, pest damage, pesticide application techniques, agricultural policies, and demand for agricultural products [14], [15]. By developing Pesticide Agricultural Shared Socio-economic Pathways (Pest-Agri-SSPs), researchers have explored different scenarios of pesticide use and emissions, highlighting the need for sustainable agricultural practices, technological advances, and better implementation of agricultural policies to decrease pesticide use and mitigate environmental impacts.…”
Section: Pesticide Use and Farming Efficiencymentioning
confidence: 99%